2018
DOI: 10.1080/09640568.2018.1435410
|View full text |Cite
|
Sign up to set email alerts
|

Climate adaptation management and institutional erosion: insights from a major Canadian port

Abstract: This paper performs an institutional analysis of the adaptation to climate change by ports, through a case study of the port of Vancouver, Canada. While previous literature has demonstrated the value of informal institutions for filling gaps left by formal institutions, the role of failed informal institutions has received less attention. Our analysis reveals how, in the case of an unprecedented challenge like climate adaptation, relying on informal institutions with less agency can actually erode the strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 62 publications
(54 reference statements)
0
10
0
Order By: Relevance
“…Several studies described cases where governance complexity undermined change or prompted reversion to the status quo (Ng et al., 2019). In a study of historic PG water governance arrangements, Mostert (2015) found that change is complex and difficult in PG, particularly if there are multiple, vested interests in the system.…”
Section: What Do We Know About Why Pg Performs Well In Some Cases But...mentioning
confidence: 99%
“…Several studies described cases where governance complexity undermined change or prompted reversion to the status quo (Ng et al., 2019). In a study of historic PG water governance arrangements, Mostert (2015) found that change is complex and difficult in PG, particularly if there are multiple, vested interests in the system.…”
Section: What Do We Know About Why Pg Performs Well In Some Cases But...mentioning
confidence: 99%
“…Various responses are possible, ranging from increased coastal defences and raising quays to moving facilities and managed retreat (Becker et al 2018;Yang et al 2018). Yet as with mitigation, work towards adaptation has in most cases stalled on the same collective action problem, whereby public and private sectors pass the buck and avoid commitment to necessary investments (Ng, Monios, and Zhang 2019). While the threats of frequent and severe storms and sea level rise are recognised, the uncertainty of if/when they will arrive in a particular location prevents marketbased rationality from attributing a clear risk and reward valuation and hence action plan for stakeholders (Ng et al 2018).…”
Section: Climate Change Adaptationmentioning
confidence: 99%
“…The potential disconnection between regional public transport and local land use planning is one such "hotspot" where previous research has suggested that regional and local authorities create integrated planning through dialog that produces agreements with no statutory status (e.g., Hrelja et al, 2017). This research on governance in public transport can be viewed as a subset of a broader body of transport research (e.g., Stead, 2016) that shares a similar analytical interest in what can be achieved through so-called "informal" or "soft" forms of governance (in such different empirical areas as port governance, e.g., Ng, Monios, & Zhang, 2018, and partnerships for delivering better bus services, e.g., Stanley & van de Velde, 2008) that inform and coordinate the actions of discrete organizations. There is a clear relationship between this research and the theory of collaboration tested in the present paper.…”
Section: What Practical Recommendations On How Tomentioning
confidence: 99%
“…The integration of regional public transport planning and local land-use planning has also been identified as a key collaborative "hotspot". More specifically, the need for collaboration in this area often arises out of tensions between local-level priorities and control of land-use planning, which clash with a more strategic regional approach to transport planning aiming to achieve urban and regional development patterns that support public transport use (Hrelja, 2015;Hrelja et al, 2017;Olesen, 2012;Pettersson & Frisk, 2016). Another key issue when establishing efficient public transport systems concerns how to provide "seamless" transport services within and across transport modes in order to facilitate the use of the public transport systems (Berman, Smith, & Bauer, 2005;O'Sullivan & Patel, 2004).…”
Section: Introductionmentioning
confidence: 99%